Pengaruh Permainan Ular Tangga Modifikasi Terhadap Kemampuan Higher Order Thinking Skill (Hots) Anak Taman Kanak-Kanak Pertiwi 1 Kantor Gubernur Padang - Ozza fahmi; Setiyo Utoyo (JCE (Journal of Childhood Education), 2025)
This research is motivated by the problem of unstimulated HOTS abilities of children in Pertiwi 1 Kindergarten, Padang Governor's Office.This happens because learning activities are always centered on teachers and learning activities that always use LKA every day so that children are easily bored and quickly bored because there are no interesting activities and are carried out every day in learning.This study aims to meet how much influence the modified snakes and ladders game has on children's HOTS abilities in Pertiwi 1 Kindergarten, Padang Governor's Office.The research method used is quantitative with an experimental approach in the form of a quasi-experiment.Using a research sample in group B5 consisting of 10 children in the experimental class and 10 children in the control class.Data analysis techniques used include normality tests, homogeneity tests and hypothesis tests.To test the difference in children's HOTS abilities before and after being given treatment.The results of the research data analysis, the average pre-test for the experimental class was 14 and 14.7 for the control group.While the average post-test for the experimental group was 21.4 and 19.7 for the control class.The difference shows that for the experimental class using the snakes and ladders game and the control class using flashcards are homogeneous.The results of the study can be said to be significant because the use of modified snakes and ladders games has the advantage of stimulating HOTS abilities in children.The advantage of this snakes and ladders game is that children can solve simple problems, analyze images and compare one image with another.Thus it can be concluded that there is an influence of the modified snakes and ladders game on the HOTS abilities of children at Pertiwi 1 Kindergarten, Padang Governor's Office.